Robotic salvage lymph node dissection for nodal-only recurrences after radical prostatectomy: Perioperative and early oncological outcomes. (June 2018) - Linxweiler, Johannes; Saar, Matthias; Al-Kailani, Zaid; Janssen, Martin; Ezziddin, Samer; Stöckle, Michael; Siemer, Stefan; Ohlmann, Carsten-Henning
Abstract: Background: Salvage lymph node dissection (sLND) – performed open or minimally-invasive - is a treatment modality that can be offered to patients with nodal recurrence after radical prostatectomy (RP), especially in times where modern imaging methods like choline- or PSMA-PET/CT are available. Yet, there are only very limited data on the safety and oncological effectiveness of robotic sLND. Methods: We retrospectively identified patients who underwent robotic sLND at our institution between 2013 and 2017 for nodal recurrence after RP, which had been diagnosed either by 18 F-choline- or 68 Ga-PSMA-PET/CT. We analyzed perioperative data and early oncological outcomes with a focus on the comparison of patients with preoperative choline- vs. those with preoperative PSMA-PET/CT. Results: We identified 36 patients who underwent robotic sLND at a median time of 45.3 months [range 3.1;228.6] after RP, with nodal recurrences detected in 25 patients by PSMA- and in 11 by choline-PET/CT. Median preoperative PSA, operation time and blood loss were 1.98 ng/ml [range 0.09;35.15], 129.5 min [range 65;202] and 50 ml [range 0;400], respectively. No high-grade complications occurred. A median number of 6.5 [range 1;25] lymph nodes were removed with a median of 1 [range 0;9] tumor-occupied node. None of the patients received any adjuvant treatment. Median postoperative PSA-change was −57% [range −100; +58] in the PSMA- and +10% [range −91; +95] in the choline-group (p = 0.015). 44% of patients in the PSMA- and 18% of patients in the choline-group experienced complete biochemical response (cBCR; PSA <0.2 ng/ml). Median time from sLND to the initiation of further therapy was 12 months [range 2;21.5] in the PSMA-group and 4.7 months [range 2.2;18.9] in the choline-group (p = 0.001). Conclusions: This is the hitherto largest series on robotic sLND for nodal recurrence after RP. Robotic sLND is a feasible therapeutic option with low morbidity, which can at least delay the initiation of further therapy – in some patients up to several years. However, the extend of sLND has to be standardized and randomized trials are needed to finally define the oncological effectiveness of this approach. Highlights: Robotic sLND has low morbidity and can be offered to patients with nodal recurrence after RP. Complete biochemical responses can be reached in up to 44% of patients. Better outcomes of sLND are seen with preoperative imaging by 68 Ga-PSMA-PET/CT compared to 18 F-Choline-PET/CT. Most sLND patients will recur and need further therapy (mostly ADT), yet the start of this therapy can be markedly delayed. The results of prospective studies have to be awaited to finally judge the oncological benefit of sLND beyond delay of ADT.